Cryopreservation of Sperm in Common Carp (Cyprinus Carpio) and Its Strain Amur Carp (Cyprinus Carpio Haematopterus): Sperm Motility and Hatching Success of Embryos - Sharma, Adita; Ram, R. N.; Prasad, Shiv (Indian Journal of Hill Farming, 2018)
The present study was conducted for comparing the performance of cryopreserved sperm of Common carp (Cyprinus carpio) with its Amur strain (Cyprinus carpio haematopterus) in monsoon season (MS) and post monsoon season (PMS). The parameters used for milt quality analysis are sperm motility percentage and motility duration. Fertilization rate, hatching rate and embryonic development were also recorded in monsoon and post monsoon season. Results of this experiment are indicative of successful cryopreservation of common carp and Amur carp sperms either by using TRIS+DMSO+Glucose or RPMI+DMSO or PBS+DMSO. In Amur carp comparison of three diluent combinations, maximum motility, fertilization rate and hatching rate were obtained with TRIS+DMSO+Glucose in both the seasons. In case of common carp, the higher percentages of viability and fertilization rate were observed in PBS+ DMSO during MS and PMS. On the premise of this test, it can be concluded that TRIS+DMSO+Glucose is the best suited combination for freezing Amur carp sperm. On the other hand, PBS+DMSO is quality combination for freezing of common carp sperm. The overall result of the present study revealed that in comparison between Amur carp and common carp, best embryonic development were found in Amur carp indicating that Amur carp performed well than common carp. It indicating that reproduction capacity of Amur carp is higher than common carp. So, if Amur carp is cultured on large scale, a high profit will be obtained which will augment fish production. In this way food security may be ensured across the globe by reducing food crisis.